AKAD NIKAH DENGAN VIDEO CALL: dalam Pandangan Habib Zain bin Ibrahim Bin Smith dalam kitab Al-Mukhtarah li Saliki Thariq Al-Akhirah - Huda, Muhammad Hasbulloh; din, Ishomud (MAQASHID, 2023)
The discussion in this research is a review of Islamic law regarding the issue of marriage contracts via video calls that have ever occurred. The data studied is the fatwa of the Ulama' of the Syafi'iyyah madzhab with more focus on the fatwa of Habib Zain bin Ibrahim bin Smith. Regarding this research, researchers tried to analyze the fatwa of Habib Zain bin Ibrahim bin Smith as the main study material. By using a literature review through technical fatwa analysis. This analysis aims to find out more deeply and critically about fatwas related to the problems above. The existing data was obtained from reading classical and contemporary jurisprudence literature, focusing more on the fatwa of Habib Zain bin Ibrahim bin Smith in the book Fawaidul Mukhtarah Li Salik Tariqil Akhirah. The data is then collected and used as a legal comparison. Through this research, the following results were obtained: Description of the practice of marriage contracts via video call. Legal fatwas that can be used as a reference if a marriage contract takes place via video call. Legal conclusions and results of fatwas regarding marriage contracts via video call. Plus there is a solution if the marriage ceremony takes place via video call.